Quantum leap Season 2 Disc 2 - Bakula, Scott; Stockwell, Dean, 1936-2021.; Belisarius Productions; Universal City Studios ([United States] : Universal Studios, 2004)
Reunite with Dr. Sam Beckett, a scientist who never knows whose body he is going to "leap" into next or when, where and at what moment in time he may find himself. Who will he be next? An undercover cop. A blind pianist. A harassed secretary. It's up to Sam to change the history of each person for the better, and hopefully complete the mission that will someday take hime home.
Side A: So help me God -- Catch a falling star -- A portrait for Troian -- Animal frat -- Side B: Another mother -- All American -- Her charm and freedom.
Title from container.
Originally broadcast as a television series.
Scott Bakula, Dean Stockwell.
MPAA rating: Not rated.
DVD, region 1, full screen presentation; Dolby Digital 2.0.
English dialogue, French or Spanish subtitles; closed-captioned.
Keywords: Time travel; DVD-Video discs; Drama; Science fiction television programs; Video recordings for the hearing impaired